The Effect of Vehicle Tie Angle on the Car Deck Lashing System Safety Factor of a Ro-Ro Ferry - Alamsyah; Suardi; Setiawan, Wira; Pawara, M. Uswah; Hariyono; Sitorus, Chris Jeremy Verian; Firmansyah, Ardi; Abdulloh, Muhammad Malik Fahad; Paroka, Daeng; Ardianti, Andi (Engineering, Technology & Applied Science Research, 2026)
This study investigates the vehicle lashing system implemented short crossing routes, such as the Balikpapan-Penajam Paser Utara route. Regulations stipulate that the maximum engagement angle should be 60°; however, they do not specify an explicit safety factor for the lashing system. Thus, this study focuses on the influence of vehicle tie angle on the safety factor of the lashing system. Modeling of the existing mild steel lashing system was carried out using Finite Element Method (FEM) numerical simulations to calculate the safety factor of the vehicle lashing system against the engagement angle, as specified in Indonesian government regulations. The results show that for all lashing system models, the von Mises stress increases linearly with the magnitude of the applied engagement angle. For Model 1, the safety factor was less than 1.0, indicating that the model is unsafe at lashing angles of 70° and 90. In contrast, other models were safe at higher lashing angles, especially Model 4, which exhibited the highest safety factor at lashing angles ranging from 30 to 90°. These results provide input to the government to consider increasing the upper limit of the vehicle system lashing angle in the regulation. A higher lashing angle will create more space on the deck of the Roll-On-/Roll-Off (Ro-Ro) ferries, potentially increasing the income of ferry operators.